HUBUNGAN SELF REGULATED LEARNING TERHADAP KEMAMPUAN SOSIAL SISWA SD NEGERI 7 REJANG LEBONG - ranti, Ranti Andita; Siti Zulaiha; Rizki Yunita Putri (STKIP Subang, 2026)
This study was motivated by the varying levels of students’ self-regulated learning and social skills. Self-regulated learning refers to students’ independence in managing, monitoring, and evaluating their learning processes, which is closely related to their ability to interact, cooperate, and adapt within the school environment. This research aims to: (1) determine the level of self-regulated learning of sixth-grade students at SD Negeri 7 Rejang Lebong, (2) identify the level of students’ social skills, and (3) to determine the relationship between self-regulated learning and social skills. This study employed a quantitative approach with a correlational research design. The population consisted of all sixth-grade students of SD Negeri 7 Rejang Lebong, totaling 50 students, and total sampling technique was used. Data were collected using questionnaires with Likert scale instruments. Instrument validity was tested using the Product Moment formula, while reliability was tested using Cronbach Alpha, resulting in coefficients of 0.713 for self-regulated learning and 0.788 for social skills. Data analysis used Product Moment correlation. The results showed that: (1) students’ self-regulated learning was in the good category, (2) students’ social skills were also in the good category, and (3) there was a significant positive relationship between self-regulated learning and social skills with a correlation value of 0.866, which is higher than r table (0.278). Thus, it can be concluded that there is a significant relationship between self-regulated learning and students’ social skills.